# Unit 1 Expressions BINGO ```Unit 1 Expressions Bingo
A-APR.1.1 &amp; A-sse.1.1
Materials Needed:
• Bingo sheet printed for each student
• Bingo chips/markers/stamps
• Printed set of verbal expressions cards
• Elmo/projector
Instructions:
 Cut out the verbal expressions cards and mix them up.
 Give each student a bingo board and enough chips to cover several
spaces.
 Select a card and project it for students to see while you read it aloud.
 Allow time for students to translate the verbal expression into an
algebraic expression. Students then find the algebraic expression on
their bingo board and mark it.
 Select another expression card and continue play until students get
bingo, or the allotted activity time ends.
A quarter of the sum of three consecutive
numbers
Kevin gets paid to mow his neighbor’s lawn. For
every week that he mows the lawn, he earns
\$25.
Myrna and Tom collect stamps and want an
expression to count their stamps in total. Tom is
bringing his stamps to Myrna’s house so that
they can count. Tom has half the stamps that
Myrna has plus four.
The local gym charges a monthly membership
fee of \$5 and \$2.25 per day.
The sum of 7 times a number n plus 5
Three times x squared
Carlos has deleted 30 messages from his
messages a day from now on.
Lynn tried to fly her kite but discovered that the
kite string was too short. If she doubles the
length of the string, it will be 28 feet long. What
is the expression to know how long was the
string?
Nadia is posting 17 tweets a day
The opposite of two p
The sum of three consecutive even numbers
where x is even
Twice the sum of three and p
Marlon is building a model boat. Every inch on
his model is equivalent to 3.5 feet on the real
boat his model is based on.
Reynaldo is saving money to buy a car. He
decides to withdraw \$50 from his savings
account for books. The amount left in his
account after the withdrawal is \$200.
The opposite reciprocal of four times b
The sum of three consecutive odd numbers
where x is odd
Mario needs to buy boxes of pizza at \$6 each but
the cost will be split between him and his
brother.
The cost of a telephone call is 75 cents plus 25
cents times the number of minutes.
The product of three consecutive numbers
The square root of the difference between a
variable and 4
Veronica is going to pay for an item using gift
cards. The clerk tells her that she will need 2 gift
cards and an additional \$3 to pay for the item.
Carmen gets paid to walk her neighbor’s dog.
For every week that she walks the dog, she
earns \$15.
Coefficient’s bakery sells donuts by the box.
There are Certain number of donuts in each box.
Josh is going to buy 10 boxes for a class field trip.
Four more than twice m
Mary is putting away savings for her college
education. Every time Mary puts a dollar in his
fund, her parents put in \$2.
The difference between 15 and the product of 5
and a number.
The quotient of y and three
There are 200 people in a soccer league divided
into teams.
Jordi post 12 messages in his own Facebook wall
every day
Mitch is trying to mail a package to his
grandmother. He already has s stamps on the
package. The postal worker tells him that he’s
going to have to double the number of stamps
on the package and then add 3 more.
The difference between two times y squared
and 5
The reciprocal of one half times v
Three less than four times y
2(3 + p)
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
0.25m + 0.75
−𝑏𝑏
4
x + (x + 2) + (x + 4)
25w
17t
10d
2m + 4
2.25d + 5
15 – 5c
-2p
Free
15w
3x2
28 – 2x = y
s = 2l
y = 3.5x
12m
6𝑝𝑝
2
x + (x + 2) + (x + 4)
200
𝑛𝑛
2g +3
2s + 3
ℎ
+4
2
2v
17t
10d
ℎ
+4
2
−𝑏𝑏
4
2y2 – 5
2(3 + p)
12m
x – 50 = 200
15 – 5c
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
200
𝑛𝑛
2.25d + 5
25w
Free
s = 2l
x + (x + 2) + (x + 4)
-2p
4y – 3
3x2
y = 3.5x
�(𝑥𝑥 – 4)
2m + 4
30 – 5m
2s + 3
17t
x(x + 1)(x + 2)
30 – 5m
x + (x + 2) + (x + 4)
-2p
2y2 – 5
2(3 + p)
2s + 3
2v
15 – 5c
15w
Free
7n + 5
25w
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
200
𝑛𝑛
6𝑝𝑝
2
ℎ
+4
2
2.25d + 5
2m + 4
10d
y = 3.5x
−𝑏𝑏
4
3x2
s = 2l
15 – 5c
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
25w
12m
x + (x + 2) + (x + 4)
30 – 5m
2m + 4
y = 3.5x
Free
s = 2l
𝑦𝑦
3
ℎ
+4
2
2.25d + 5
-2p
28 – 2x = y
0.25m + 0.75
2(3 + p)
6𝑝𝑝
2
�(𝑥𝑥 – 4)
x – 50 = 200
x(x + 1)(x + 2)
−𝑏𝑏
4
2y2 – 5
2g +3
7n + 5
y = 3.5x
30 – 5m
2s + 3
4y – 3
2g +3
Free
200
𝑛𝑛
�(𝑥𝑥 – 4)
x + (x + 2) + (x + 4)
15w
0.25m + 0.75
2y2 – 5
x + (x + 2) + (x + 4)
12m
x – 50 = 200
7n + 5
-2p
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
15 – 5c
ℎ
+4
2
3x2
2.25d + 5
6𝑝𝑝
2
s = 2l
2(3 + p)
12m
2s + 3
2g +3
15 – 5c
2y2 – 5
10d
15w
Free
7n + 5
3x2
x + (x + 2) + (x + 4)
17t
25w
4y – 3
200
𝑛𝑛
−𝑏𝑏
4
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
x – 50 = 200
s = 2l
𝑦𝑦
3
6𝑝𝑝
2
x + (x + 2) + (x + 4)
x(x + 1)(x + 2)
2.25d + 5
2(3 + p)
2y2 – 5
4y – 3
25w
y = 3.5x
-2p
x(x + 1)(x + 2)
s = 2l
x – 50 = 200
2(3 + p)
10d
12m
Free
𝑦𝑦
3
�(𝑥𝑥 – 4)
30 – 5m
2s + 3
ℎ
+4
2
2m + 4
2v
15 – 5c
3x2
−𝑏𝑏
4
7n + 5
0.25m + 0.75
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
7n + 5
−𝑏𝑏
4
x(x + 1)(x + 2)
𝑦𝑦
3
15 – 5c
ℎ
+4
2
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
4y – 3
28 – 2x = y
y = 3.5x
2(3 + p)
2.25d + 5
x + (x + 2) + (x + 4)
x + (x + 2) + (x + 4)
Free
3x2
17t
25w
30 – 5m
x – 50 = 200
12m
-2p
15w
�(𝑥𝑥 – 4)
0.25m + 0.75
2s + 3
10d
�(𝑥𝑥 – 4)
15 – 5c
x – 50 = 200
30 – 5m
2v
-2p
Free
2.25d + 5
y = 3.5x
−𝑏𝑏
4
2m + 4
2(3 + p)
200
𝑛𝑛
28 – 2x = y
𝑦𝑦
3
17t
6𝑝𝑝
2
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
15w
x + (x + 2) + (x + 4)
x(x + 1)(x + 2)
4y – 3
7n + 5
𝑦𝑦
3
200
𝑛𝑛
15w
25w
-2p
28 – 2x = y
2y2 – 5
15 – 5c
30 – 5m
x + (x + 2) + (x + 4)
2s + 3
Free
7n + 5
17t
y = 3.5x
2.25d + 5
3x2
10d
2g +3
s = 2l
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
−𝑏𝑏
4
ℎ
+4
2
4y – 3
2(3 + p)
−𝑏𝑏
4
200
𝑛𝑛
2m + 4
15 – 5c
17t
2.25d + 5
Free
-2p
2g +3
2y2 – 5
30 – 5m
3x2
12m
x – 50 = 200
0.25m + 0.75
4y – 3
28 – 2x = y
𝑦𝑦
3
2(3 + p)
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
6𝑝𝑝
2
s = 2l
x(x + 1)(x + 2)
x + (x + 2) + (x + 4)
ℎ
+4
2
-2p
ℎ
+4
2
2y2 – 5
x – 50 = 200
2.25d + 5
12m
x + (x + 2) + (x + 4)
x(x + 1)(x + 2)
Free
2(3 + p)
0.25m + 0.75
30 – 5m
10d
𝑦𝑦
3
�(𝑥𝑥 – 4)
7n + 5
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
2g +3
15 – 5c
17t
2m + 4
y = 3.5x
3x2
s = 2l
200
𝑛𝑛
30 – 5m
x – 50 = 200
3x2
𝑦𝑦
3
2m + 4
17t
s = 2l
2s + 3
Free
-2p
25w
12m
�(𝑥𝑥 – 4)
4y – 3
2(3 + p)
x + (x + 2) + (x + 4)
ℎ
+4
2
y = 3.5x
200
𝑛𝑛
28 – 2x = y
6𝑝𝑝
2
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
−𝑏𝑏
4
2v
15 – 5c
17t
200
𝑛𝑛
ℎ
+4
2
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
�(𝑥𝑥 – 4)
s = 2l
2y2 – 5
4y – 3
3x2
2.25d + 5
2s + 3
x – 50 = 200
0.25m + 0.75
y = 3.5x
Free
12m
2(3 + p)
10d
x + (x + 2) + (x + 4)
25w
28 – 2x = y
15 – 5c
2m + 4
2g +3
−𝑏𝑏
4
6𝑝𝑝
2
17t
15w
ℎ
+4
2
2.25d + 5
𝑦𝑦
3
s = 2l
x – 50 = 200
2v
4y – 3
Free
28 – 2x = y
3x2
25w
30 – 5m
x(x + 1)(x + 2)
2m + 4
2s + 3
12m
10d
2y2 – 5
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
200
𝑛𝑛
x + (x + 2) + (x + 4)
y = 3.5x
30 – 5m
2g +3
x – 50 = 200
2m + 4
0.25m + 0.75
17t
10d
𝑦𝑦
3
�(𝑥𝑥 – 4)
12m
x(x + 1)(x + 2)
15w
Free
2.25d + 5
y = 3.5x
7n + 5
15 – 5c
x + (x + 2) + (x + 4)
2y2 – 5
ℎ
+4
2
−𝑏𝑏
4
28 – 2x = y
s = 2l
6𝑝𝑝
2
25w
10d
4y – 3
2v
28 – 2x = y
0.25m + 0.75
200
𝑛𝑛
�(𝑥𝑥 – 4)
7n + 5
x – 50 = 200
2y2 – 5
y = 3.5x
2(3 + p)
Free
-2p
2g +3
2m + 4
25w
2.25d + 5
x + (x + 2) + (x + 4)
30 – 5m
15 – 5c
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
15w
6𝑝𝑝
2
x + (x + 2) + (x + 4)
200
𝑛𝑛
12m
2g +3
2.25d + 5
�(𝑥𝑥 – 4)
15 – 5c
17t
2s + 3
ℎ
+4
2
−𝑏𝑏
4
y = 3.5x
x + (x + 2) + (x + 4)
Free
15w
x – 50 = 200
3x2
x(x + 1)(x + 2)
28 – 2x = y
30 – 5m
4y – 3
x + (x + 2) + (x + 4)
2m + 4
7n + 5
-2p
2y2 – 5
15w
2y2 – 5
2g +3
s = 2l
x + (x + 2) + (x + 4)
2s + 3
�(𝑥𝑥 – 4)
𝑦𝑦
3
x + (x + 2) + (x + 4)
0.25m + 0.75
15 – 5c
2m + 4
30 – 5m
Free
-2p
2.25d + 5
7n + 5
2(3 + p)
10d
28 – 2x = y
17t
y = 3.5x
−𝑏𝑏
4
6𝑝𝑝
2
x – 50 = 200
𝑦𝑦
3
�(𝑥𝑥 – 4)
2s + 3
10d
15w
y = 3.5x
x – 50 = 200
12m
Free
x(x + 1)(x + 2)
2m + 4
4y – 3
3x2
x + (x + 2) + (x + 4)
7n + 5
s = 2l
30 – 5m
-2p
2(3 + p)
6𝑝𝑝
2
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
2y2 – 5
17t
2v
ℎ
+4
2
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
y = 3.5x
2s + 3
x + (x + 2) + (x + 4)
6𝑝𝑝
2
𝑦𝑦
3
200
𝑛𝑛
2(3 + p)
15 – 5c
x(x + 1)(x + 2)
Free
3x2
2.25d + 5
28 – 2x = y
15w
-2p
�(𝑥𝑥 – 4)
s = 2l
0.25m + 0.75
2y2 – 5
7n + 5
12m
17t
4y – 3
−𝑏𝑏
4
200
𝑛𝑛
2s + 3
-2p
2y2 – 5
12m
3x2
0.25m + 0.75
2v
x + (x + 2) + (x + 4)
6𝑝𝑝
2
28 – 2x = y
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
Free
ℎ
+4
2
7n + 5
25w
y = 3.5x
15w
2(3 + p)
17t
2g +3
30 – 5m
2.25d + 5
x(x + 1)(x + 2)
10d
y = 3.5x
ℎ
+4
2
2y2 – 5
𝑦𝑦
3
x + (x + 2) + (x + 4)
2v
200
𝑛𝑛
30 – 5m
28 – 2x = y
x(x + 1)(x + 2)
7n + 5
10d
Free
x – 50 = 200
2(3 + p)
2s + 3
�(𝑥𝑥 – 4)
6𝑝𝑝
2
-2p
15w
2m + 4
15 – 5c
2g +3
s = 2l
4y – 3
15 – 5c
2.25d + 5
17t
7n + 5
s = 2l
x + (x + 2) + (x + 4)
4y – 3
2y2 – 5
2(3 + p)
30 – 5m
x(x + 1)(x + 2)
12m
Free
x + (x + 2) + (x + 4)
10d
28 – 2x = y
2g +3
2m + 4
0.25m + 0.75
x – 50 = 200
15w
200
𝑛𝑛
2v
ℎ
+4
2
25w
200
𝑛𝑛
2.25d + 5
2y2 – 5
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
28 – 2x = y
𝑦𝑦
3
2m + 4
12m
17t
−𝑏𝑏
4
2s + 3
30 – 5m
Free
x + (x + 2) + (x + 4)
y = 3.5x
15w
7n + 5
-2p
25w
x – 50 = 200
4y – 3
x(x + 1)(x + 2)
2(3 + p)
2g +3
ℎ
+4
2
x(x + 1)(x + 2)
𝑦𝑦
3
2v
12m
x + (x + 2) + (x + 4)
10d
2m + 4
3x2
0.25m + 0.75
7n + 5
y = 3.5x
2y2 – 5
Free
2g +3
�(𝑥𝑥 – 4)
x – 50 = 200
15w
4y – 3
−𝑏𝑏
4
s = 2l
25w
200
𝑛𝑛
x + (x + 2) + (x + 4)
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
17t
ℎ
+4
2
4y – 3
12m
-2p
15w
x – 50 = 200
x(x + 1)(x + 2)
2s + 3
25w
7n + 5
2y2 – 5
y = 3.5x
Free
𝑦𝑦
3
�(𝑥𝑥 – 4)
6𝑝𝑝
2
x + (x + 2) + (x + 4)
2m + 4
0.25m + 0.75
200
𝑛𝑛
10d
3x2
2v
2g +3
2.25d + 5
15 – 5c
2.25d + 5
2v
2g +3
4y – 3
2m + 4
30 – 5m
-2p
15w
28 – 2x = y
7n + 5
Free
10d
0.25m + 0.75
2s + 3
s = 2l
17t
200
𝑛𝑛
−𝑏𝑏
4
2y2 – 5
6𝑝𝑝
2
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
𝑦𝑦
3
x + (x + 2) + (x + 4)
x + (x + 2) + (x + 4)
ℎ
+4
2
2y2 – 5
y = 3.5x
2v
12m
28 – 2x = y
3x2
−𝑏𝑏
4
𝑦𝑦
3
2g +3
x + (x + 2) + (x + 4)
Free
7n + 5
-2p
2m + 4
s = 2l
15w
30 – 5m
x + (x + 2) + (x + 4)
4y – 3
25w
15 – 5c
2.25d + 5
2(3 + p)
6𝑝𝑝
2
4y – 3
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
2g +3
2m + 4
200
𝑛𝑛
12m
2v
2y2 – 5
2s + 3
x + (x + 2) + (x + 4)
15w
28 – 2x = y
Free
�(𝑥𝑥 – 4)
2(3 + p)
0.25m + 0.75
x + (x + 2) + (x + 4)
s = 2l
10d
2.25d + 5
x(x + 1)(x + 2)
3x2
17t
𝑦𝑦
3
-2p
6𝑝𝑝
2
2v
x – 50 = 200
x + (x + 2) + (x + 4)
25w
2g +3
�(𝑥𝑥 – 4)
x(x + 1)(x + 2)
Free
-2p
4y – 3
15w
2m + 4
s = 2l
28 – 2x = y
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
𝑦𝑦
3
10d
200
𝑛𝑛
3x2
17t
x + (x + 2) + (x + 4)
−𝑏𝑏
4
y = 3.5x
2s + 3
15w
2y2 – 5
3x2
200
𝑛𝑛
25w
-2p
15 – 5c
30 – 5m
s = 2l
2v
𝑦𝑦
3
y = 3.5x
x + (x + 2) + (x + 4)
Free
x – 50 = 200
10d
12m
2s + 3
2m + 4
x + (x + 2) + (x + 4)
[𝑥𝑥 + (𝑥𝑥 + 1) + (𝑥𝑥 + 2)]
4
�(𝑥𝑥 – 4)
x(x + 1)(x + 2)
2(3 + p)
28 – 2x = y
12m
2y2 – 5
0.25m + 0.75
y = 3.5x
2(3 + p)
30 – 5m
2s + 3
4y – 3
x + (x + 2) + (x + 4)
2g +3
2.25d + 5
15 – 5c
Free
28 – 2x = y
x – 50 = 200
7n + 5
10d
-2p
s = 2l
25w
6𝑝𝑝
2
𝑦𝑦
3
�(𝑥𝑥 – 4)
−𝑏𝑏
4
ℎ
+4
2
12m
25w
x + (x + 2) + (x + 4)
x – 50 = 200
10d
-2p
y = 3.5x
2s + 3
Free
−𝑏𝑏
4
200
𝑛𝑛
15w
7n + 5
2g +3
x(x + 1)(x + 2)
3x2
2v
ℎ
+4
2
𝑦𝑦
3
28 – 2x = y
x + (x + 2) + (x + 4)
2y2 – 5
s = 2l
17t
6𝑝𝑝
2
6𝑝𝑝
2
15 – 5c
30 – 5m
y = 3.5x
10d
7n + 5
-2p
2.25d + 5
25w
Free
x – 50 = 200
x + (x + 2) + (x + 4)
15w
2m + 4
2g +3
�(𝑥𝑥 – 4)
−𝑏𝑏
4
0.25m + 0.75
28 – 2x = y
2(3 + p)
12m
200
𝑛𝑛
2s + 3
3x2
ℎ
+4
2
```